OPEN EDUCATIONAL RESOURCES IN THE CONTEXT OF SCHOOL EDUCATION: BARRIERS AND POSSIBLE SOLUTIONS - Richter, Thomas; Kretschmer, Thomas; Stracke, Christian M.; Bruce, Alan; Hoel, Tore; Megalou, Elina; Mazar, Ildiko; Sotirou, Sofoklis (European Scientific Journal, ESJ, 2014)
Due to the increasing professional mobility of their parents, pupils often find themselves in new and unfamiliar learning scenarios in foreign contexts and countries. Besides having to leave their familiar environments, these pupils additionally may face language barriers, different curricula, and have to cope with foreign cultures. Printed textbooks, which are the most commonly used educational resources in schools, provide little support for these pupils to manage the new challenges. Teachers are the professionals designated to provide the necessary support. However, they often may not fully appreciate the pupils’ individual challenges. Possible solutions could be the provision of alternative learning contents in the pupils’ native languages and an international open exchange of knowledge and experiences amongst schoolteachers. These issues are addressed by the Open Discovery Space platform. In order to empower this platform to provide the best possible support to teachers, we explored barriers to adoption of Open Educational Practices in the context of school education and asked for manageable solutions. The investigation took place in an action research scenario. After an introduction of the ODS project, we will present the identified barriers and recommendations for solutions to overcome these, and the mechanisms which we are going to implement in the ODS platform in order to provide the best possible support to the community.